Protective effect of nerolidol-loaded in nanospheres against cerebral damage caused by Trypanosoma evansi - Baldissera M.D. (2018)
© 2018, Springer-Verlag GmbH Germany, part of Springer Nature.Trypanosoma evansi is a zoonotic parasite associated with high animal mortality that has gained importance due to its capacity to infect humans. Recently, some evidences have demonstrated that T. evansi infection causes severe genotoxic and cytotoxic damage in brain cells, contributing to the pathogenesis and clinical signs of the disease. In this sense, the aim of this study was to evaluate whether nerolidol-loaded in nanospheres, a natural compound with trypanocidal and neuroprotective effects, is able to protect the brain tissue from the cytotoxic and genotoxic effects found during T. evansi infections. Trypanosoma evansi induced brain genotoxic effects through increased damage index (DI) and frequency of damage (FD) when compared to the control group. Moreover, T. evansi induced cytotoxic effects through the reduction of brain cell viability compared to the control group. The metabolites of nitric oxide (NOx) increased in infected animals compared to the control group. The treatment with nerolidol-loaded in nanospheres prevented the increase on brain DI, FD, and NOx levels, as well as the reduction on cell viability. Based on these evidences, these results confirm that T. evansi induces genotoxic and cytotoxic damage mediated by the upregulation of NOx levels. The most important finding is that nerolidol-loaded in nanospheres was able to prevent DNA damage and cell mortality through the modulation of brain NOx levels. In summary, this treatment can be considered an interesting approach to prevent T. evansi brain damage due its anti-inflammatory property.